Determinan Keputusan Pelaku Umkm Dalam Memilih Pinjaman Online Sebagai Alternatif Pendanaan - Putu Arik Lesmawan; I Gede Agus Pertama Yudantara (Universitas Pendidikan Ganesha, 2022)
This study aims to analyze the factors that influence the decisionmaking process of small business ventures in choosing online loans (peer to peer lending) as an alternative funding. This type of research is quantitative research that uses purposive sampling method with a sample of 100 owners small business ventures. This research data uses primary data obtained by distributing questionnaires to owner small business ventures who do business in Buleleng Regency and have used online loans. The method used in this research is descriptive analysis. The results of this study indicate four factors that positively and significantly influence the decisionmaking of owner small business ventures in choosing online loans as an alternative funding (1) Motivation (2) Experience (3) Credit Elements (4) Marketing. While the attitude and demographic factors have a negative and significant effect on the decisionmaking of owner small business ventures in choosing online loans as an alternative funding. Motivation is the most significant factor influencing the decisions of owner small business ventures in making online loans as an alternative funding Keywords : Loans Online, Financial Technology, Small Business Ventures